Life‐stage differences in spatial genetic structure in an irruptive forest insect: implications for dispersal and spatial synchrony. Issue 2 (9th January 2015) - James, Patrick M. A.; Cooke, Barry; Brunet, Bryan M. T.; Lumley, Lisa M.; Sperling, Felix A. H.; Fortin, Marie‐Josée; Quinn, Vanessa S.; Sturtevant, Brian R.
Abstract Dispersal determines the flux of individuals, energy and information and is therefore a key determinant of ecological and evolutionary dynamics. Yet, it remains difficult to quantify its importance relative to other factors. This is particularly true in cyclic populations in which demography, drift and dispersal contribute to spatio‐temporal variability in genetic structure. Improved understanding of how dispersal influences spatial genetic structure is needed to disentangle the multiple processes that give rise to spatial synchrony in irruptive species. In this study, we examined spatial genetic structure in an economically important irruptive forest insect, the spruce budworm (Choristoneura fumiferana) to better characterize how dispersal, demography and ecological context interact to influence spatial synchrony in a localized outbreak. We characterized spatial variation in microsatellite allele frequencies using 231 individuals and seven geographic locations. We show that (i) gene flow among populations is likely very high (Fst ≈ 0); (ii) despite an overall low level of genetic structure, important differences exist between adult (moth) and juvenile (larvae) life stages; and (iii) the localized outbreak is the likely source of moths captured elsewhere in our study area. This study demonstrates the potential of using molecular methods to distinguish residents from migrants and for understanding how dispersal contributes to spatial synchronization. In irruptive populations, the strength of genetic structure depends on the timing of data collection (e.g. trough vs. peak), location and dispersal. Taking into account this ecological context allows us to make more general characterizations of how dispersal can affect spatial synchrony in irruptive populations.